2017
DOI: 10.1111/jeb.13219
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling sex allocation in a viviparous reptile with temperature‐dependent sex determination: a multifactorial approach

Abstract: Females are predicted to alter sex allocation when ecological, physiological and behavioural variables have different consequences on the fitness of male and female offspring. Traditionally, tests of sex allocation have examined single causative factors, often ignoring possible interactions between multiple factors. Here, we used a multifactorial approach to examine sex allocation in the viviparous skink, Niveoscincus ocellatus. We integrated a 16-year observational field study with a manipulative laboratory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…It is unlikely that other environmental factors contributed to this effect, as previous research has demonstrated that such factors, including maternal condition at ovulation, and food availability and quality during gestation, do not affect parturition date in this species. (Cadby et al 2011, Gruber et al 2018.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unlikely that other environmental factors contributed to this effect, as previous research has demonstrated that such factors, including maternal condition at ovulation, and food availability and quality during gestation, do not affect parturition date in this species. (Cadby et al 2011, Gruber et al 2018.…”
Section: Discussionmentioning
confidence: 99%
“…To explore population‐mean–level response of parturition dates to temperature, we first fit a linear mixed model (LMM) with mean cohort parturition date as a response variable. We have previously shown that factors other than temperature, including environmental variables (humidity, cloud cover, and wind speed; Cadby et al 2010), food quality during gestation (Cadby et al 2011), females’ condition at ovulation and food availability during gestation and their interactions with temperature (Gruber et al 2018) do not affect birth dates in N. ocellatus . We, therefore, included the site‐specific mean maximum daytime temperature during the gestation period (October 1–December 31 and October 15–January 15 for the lowland and highland sites, respectively (Pen et al 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, in a low-elevation population, sex ratios correlate with temperature [22]; sex ratios are female-biased in warm seasons/developmental conditions and male-biased in cool seasons/developmental conditions [26,27]. The populationspecific sex ratio response to temperature observed in C. ocellatus in the wild has been replicated by manipulating maternal thermal opportunity in the laboratory [22,[26][27][28][29][30]. Low-elevation females subjected to cooler short basking treatments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…10 h) produce female-biased cohorts [29,30]. By contrast, highelevation females subjected to the same thermal regimes produce sex parity cohorts [22,[26][27][28][29][30]. An adaptive explanation for these patterns is that the production of males or females is favoured at different temperatures at low elevation because the concomitant variation in birth date has sex-specific fitness consequences.…”
Section: Introductionmentioning
confidence: 99%